Role of corporate branding, customer involvement and customer relationship proneness in luxury fashion branding Peranan Penjenamaan Korporat, Hubungan Pelanggan, dan Penglibatan Pelanggan dalam Barang Berjenama Mahal - Amin, M. (Penerbit Universiti Kebangsaan Malaysia, 2019)
The main purpose of the current research is to develop and test a theoretical framework that captures the role of corporate branding (corporate association, symbolic benefits, and functional benefits), customer involvement and customer relationship proneness on customers emotional attachment and brand loyalty in the luxury fashion industry. The nature of this study is quantitative, cross-sectional and non-contrived. This study used a convenient sampling technique for the collection of data. Data were gathered from 315 customers who used to buy luxury fashion brands. This study has adopted a causal analytical approach by which hypotheses were developed and tested. For data analysis, correlation, regression, and descriptive statistics tests were carried out with the help of SPSS and mediation analysis was carried through AMOS. Findings approved that corporate association; symbolic benefits have limited impact on brand loyalty while functional benefits customer involvement and customer relationship proneness have a significant impact on brand loyalty. Findings suggest that emotional attachment fully mediates the relationship of corporate association, symbolic benefits, customer involvement, and brand loyalty, while emotional attachment partially mediates the relationship of functional benefits, customer relationship proneness, and brand loyalty. Â© 2019 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.